PENERAPAN TEORI BRUNER DAN PETA KONSEP DALAM MENINGKATKAN PENALARAN DAN PEMAHAMAN KONSEP MATEMATIKA - Ardat Ardat (UIN Sumatera Utara Medan, 2014)
This study starts from the low ability of reasoning and understanding of the math concepts students with the root of the problems caused by the use of teachers teaching model less relevant and very limited use of learning media. The study aims to determine: (1) whether the application of Bruner's theory with the help of concept maps can enhance students 'mathematical reasoning, (2) whether the application of Bruner's theory with the help of concept maps can enhance students' understanding of concepts, and (3) describe the activity levels of students in the application of theory Bruner with the help of concept maps. This research a classroom action research. Subjects in this study were students of class XI SMA 20 field totaling 40 people. Object of study is the increase in students' mathematical reasoning and understanding through learning to use Bruner's theory with the help of a concept map on the subject of Opportunity. The results of the data analysis an average score of 72.2 mastery of prerequisite. From the results of the study concluded that the application of mathematics learning using Bruner's theory with the help of concept maps can enhance students 'reasoning and understanding of mathematics, and their lessons take place either by reviewing the observations of students' activities. Based on this conclusion it is expected that the findings of this study can be used as a reference for the improvement of reasoning and understanding of math concepts students